2002
DOI: 10.1002/meet.1450390107
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between learning style preferences and teaching collaboration skills and technology: An exploratory study

Abstract: This paper reports on an exploratory study that investigates the relationship between participants' learning style preferences and their perceptions of a professional workshop on collaboration and technology to support collaboration. The Learning Preference Scale‐Students (LPSS) (Owens & Barnes, 1992) was administered to identify participants' learning style preferences as cooperative, competitive and/or individualized. Using cluster analysis two groups, or categories, of learning style preferences among the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Moreover, students' (dis)likes in instruction are merely one possible student characteristic that gave rise to the ambiguous findings on students' course experiences. Other educational student variables, such as a student's learning style (Kim & Sonnenwald, 2002;Vermunt & Vermetten, 2004), prior knowledge (Tobias, 1994), level of extrinsic/intrinsic motivation (Boekaerts, 1995;Pintrich, 1999), intelligence and achievement (Friedman & Friedman, 1980), and background characteristics such as age, gender, socio-economic status, might add to the further exploration and elaboration of the model and help to explain at least part of the currently 70% unexplained variance in the results. Hence, the quest for other influencing characteristics, directly or indirectly related to these perceptions, needs to continue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, students' (dis)likes in instruction are merely one possible student characteristic that gave rise to the ambiguous findings on students' course experiences. Other educational student variables, such as a student's learning style (Kim & Sonnenwald, 2002;Vermunt & Vermetten, 2004), prior knowledge (Tobias, 1994), level of extrinsic/intrinsic motivation (Boekaerts, 1995;Pintrich, 1999), intelligence and achievement (Friedman & Friedman, 1980), and background characteristics such as age, gender, socio-economic status, might add to the further exploration and elaboration of the model and help to explain at least part of the currently 70% unexplained variance in the results. Hence, the quest for other influencing characteristics, directly or indirectly related to these perceptions, needs to continue.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in course satisfaction were revealed for all factors. Moreover, Kim and Sonnenwald (2002) argue, on the basis of empirical evidence, that learning style should be considered as a potential variable that influences learning outcomes and preferences. Student achievement is also often related to learning/teaching preferences (Salamonson & Lantz, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that online learning can be very effective in addressing students" learning styles, activity preferences, and self and group evaluation methods. Kim and Sonnenwald found that learning style preferences (cooperative, competitive and/or individualized) influenced how students perceived collaborative practices and outcomes [19].…”
Section: Possible Solutions Through Collaboration and Creativitymentioning
confidence: 99%
“…It is widely believed that no single individual, group, or profession can possibly address all of the relevant knowledge and skills to resolve increasingly complex, multifaceted problems facing the world today [19]. Paulus and Nijstad [24] conducted an in-depth analysis of the benefits and pitfalls of group creativity which can lead to innovations, defined as the creative ideas that fundamentally change the culture.…”
Section: Possible Solutions Through Collaboration and Creativitymentioning
confidence: 99%
“…Because learners' learning style preference (LSP)s can be a major factor which influences the effectiveness of any learning programme [12]. Valenta et al [13] conclude that there is a need for future research to understand the relationship between learning styles and learning experience of online learners.…”
Section: Introductionmentioning
confidence: 99%